2013
DOI: 10.1177/0957926513496354
|View full text |Cite
|
Sign up to set email alerts
|

Trust, talk and the dictaphone: Tracing the discursive accomplishment of trust in a surgical consultation

Abstract: Using discourse analytical methods, this article examines the interactional accomplishment of trust. Focusing on a case study drawn from a corpus of 28 surgical consultations collected in a gastro-intestinal clinic, it traces the trust-building process in a specific, communicatively challenging encounter where the patient is seeking a second opinion following an operation that she deems unsuccessful. Discourse analytical findings make visible the doctor’s strategic interactional work to build interpersonal tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Building rapport is a core ingredient in developing a therapeutic relationship between nurses and patients, and research examining social aspects of nurse–patient interactions found that small talk and humour is skilfully integrated with the clinical aspects of patient care by effective nurses (Holmes & Major, ). O'Grady et al (: 9) also found that small talk was ‘purposeful and closely intertwined with the pursuit of clinical goals’. Similarly, the RNs who participated in this research used humour and small talk in the interactions with their patients.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Building rapport is a core ingredient in developing a therapeutic relationship between nurses and patients, and research examining social aspects of nurse–patient interactions found that small talk and humour is skilfully integrated with the clinical aspects of patient care by effective nurses (Holmes & Major, ). O'Grady et al (: 9) also found that small talk was ‘purposeful and closely intertwined with the pursuit of clinical goals’. Similarly, the RNs who participated in this research used humour and small talk in the interactions with their patients.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Good communication skills form a platform for building good nurse–patient relationships, with rapport being a core tenet that underpins effective and compassionate nursing care (Candlin, ; SmithBattle, Leander, Westhus, Freed, & McLaughlin, ). Rapport is defined as the interpersonal experience of harmony, warmth and ‘feeling comfortable with one another’ (Belcher & Jones, , p. 146; O'Grady, Dahm, Roger, & Yates, ). It is distinct from trust which is ‘confidence that the other party will act in one's best interests’ (O'Grady et al, , p. 9), although the two terms are often used interchangeably.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations